The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jca.21338
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange rapidly improves cardiac allograft function in patients with presumed antibody‐mediated rejection

Abstract: The rapid improvement in allograft function in our patients is most likely due to TPE as other pharmacologic interventions have longer onset. TPE should be considered a first-line intervention in the setting of pAMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Antibody‐mediated rejection (AMR) may be treated with TPE along with immunosuppressive medications; however, the evidence supporting it as a treatment option is observational . If the patient has severe allograft dysfunction, it is not unreasonable to initiate TPE emergently before a definite diagnosis is made . TPE can be performed daily for the first 2 to 3 days and then every other day for a total of five to seven procedures, with the goal to quickly remove implicated donor‐specific antibodies (DSAs) and/or inflammatory mediators .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody‐mediated rejection (AMR) may be treated with TPE along with immunosuppressive medications; however, the evidence supporting it as a treatment option is observational . If the patient has severe allograft dysfunction, it is not unreasonable to initiate TPE emergently before a definite diagnosis is made . TPE can be performed daily for the first 2 to 3 days and then every other day for a total of five to seven procedures, with the goal to quickly remove implicated donor‐specific antibodies (DSAs) and/or inflammatory mediators .…”
Section: Resultsmentioning
confidence: 99%
“…5 If the patient has severe allograft dysfunction, it is not unreasonable to initiate TPE emergently before a definite diagnosis is made. 9 TPE can be performed daily for the first 2 to 3 days and then every other day for a total of five to seven procedures, with the goal to quickly remove implicated donorspecific antibodies (DSAs) and/or inflammatory mediators. 5 The replacement fluid usually is 5% albumin unless the patient is on an anticoagulant medication and/or there are abnormalities of the coagulation profile (e.g., hypofibrinogenemia, high PT/INR/aPTT), active bleeding, and/or immediately before or after an invasive procedure, when plasma may be indicated for at least part of the replacement fluid, usually toward the end of the procedure.…”
Section: Cardiac Transplantationmentioning
confidence: 99%
“…However, it also highlights the difficulty in determining the optimal treatment schedule and number of TPE procedures. In the literature, with regards to AMR treatment, as few as 2 and as many as 19 TPE procedures have been used . Additional studies are needed to determine the optimal number of TPE procedures for each TPE cardiac transplant indication and to determine whether a more individualized approach to TPE is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…10 Across many studies of cardiac transplantation, AMR is a common use of TPE 2 ; however, as we found in our study, TPE is also frequently used for treatment of elevated PRA antibodies or positive HLA antibodies and positive crossmatch. 6,7,40 Given the high incidence of TPE use for these indications, TPE use for positive crossmatch status and positive HLA antibodies/PRA should be considered in the next iteration of the ASFA guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation